Ronco habitual e apnéia obstrutiva observada em adultos: estudo de base populacional, Pelotas, RS Habitual snoring and obstructive sleep apnea in adults: population-based study in Southern Brazil - Ricardo B Noal; Ana M B Menezes; Simone F Canani; Fernando V Siqueira (Universidade de São Paulo, 2008)
OBJETIVO: Estimar a prevalência de ronco habitual e apnéia obstrutiva observada e fatores associados. MÉTODOS: Estudo transversal com amostra representativa de 3.136 adultos, com 20 anos ou mais, residentes em Pelotas, Rio Grande do Sul, em 2005. Informações sobre os desfechos e variáveis demográficas, socioeconômicas, comportamentais e antropométricas foram coletadas por meio de questionário. A análise estatística bruta e ajustada foi realizada utilizando-se teste exato de Fisher ou qui-quadrado de tendência linear e regressão de Poisson, respectivamente. RESULTADOS: A prevalência encontrada de ronco habitual foi de 50,5% (IC 95%: 48,1;52,8) e de apnéia obstrutiva de 9,9% (IC 95%: 8,7;11,2). Na análise ajustada, o relato de ronco foi maior nos homens (Razão de Prevalências - RP=1,25; IC 95%: 1,16;1,34), nos idosos (RP=1,62; IC 95%: 1,46;1,80), nos tabagistas (RP=1,15; IC 95%: 1,07;1,25), nos alcoolistas (RP=1,17; IC 95%: 1,03;1,31) e nos obesos (RP 1,71, IC95% 1,55;1,88). O relato de apnéia obstrutiva foi maior nos homens (RP=2,05; IC 95%: 1,67;2,52), nos idosos (RP=2,23; IC 95%: 1,64;3,03), nos tabagistas (RP=1,60; IC 95%: 1,25;2,05) e nos obesos (RP=2,61; IC 95%: 1,97;3,47). CONCLUSÕES: Ronco habitual e apnéia obstrutiva foram sintomas comuns na população estudada. Fatores de risco conhecidos como sexo masculino e idade entre quarta e quinta décadas de vida não são modificáveis. Entretanto, tabagismo, alcoolismo e obesidade também associados aos desfechos, devem ser identificados e tratados na população geral. OBJECTIVE: To estimate the prevalence of habitual snoring and obstructive sleep apnea and their factors associated. METHODS: Cross-sectional study with a representative sample comprising 3,136 adults (>20 years) living in the city of Pelotas, Southern Brazil, in 2005. A questionnaire was used to collect information on demographic, socioeconomic, behavioral and anthropometric variables and outcomes. Crude and adjusted statistical analysis using Fisher exact test and chi-square test for linear trend and a multivariate analysis through Poisson regression model were carried out, respectively. RESULTS: The prevalence of habitual snoring was 50.5% (95% CI: 48.1;52.8) and obstructive sleep apnea was 9.9% (95% CI: 8.7;11.2). After adjustment, the risk of habitual snoring was greater in males (prevalence ratio [PR]=1.25, 95% CI: 1.16;1.34), elderly people (PR=1.62, 95% CI: 1.46;1.80), current smokers (PR=1.15, 95% CI: 1.07;1.25), alcohol users (PR=1.17, 95% CI: 1.03;1.31) and obese people (PR=1.71, 95% CI: 1.55;1.88). The risk of obstructive sleep apnea was greater in males (PR=2.05, 95% CI: 1.67;2.52), elderly people (PR=2.23, 95% CI: 1.64;3.03), current smokers (PR=1.60, 95% CI: 1.25;2.05) and obese people (PR=2.61, 95% CI: 1.97;3.47). CONCLUSIONS: In the studied population, habitual snoring and obstructive sleep apnea were common symptoms. Well-known risk factors such as male gender and age between 40 and 60 years are not modifiable. However, smoking, alcohol use and obesity need to be identified and treated in general population.